Responsible Leadership and Workforce Agility in Private Banking: The Role of Psychological Empowerment - Azmy, Ahmad; Tania Zahra, Luthfiyyah Leoni; Pujianto, Teten (Universitas Gadjah Mada, 2025)
Introduction/Main Objectives: This research examines the Effects of responsible Leadership and psychological empowerment on workforce agility. Background Problems: Implementing workforce agility is still not optimal in banking. Workforce agility is needed to improve the quality of financial service business, so predictors of responsible leadership and psychological empowerment are needed as supporting components. Novelty: This study focuses on the implications of responsible leadership on workforce agility in the banking business in direct and indirect ways. The uniqueness lies in using psychological empowerment as a mediator to prove the indirect influence on workforce agility. Research Methods: This study uses a purposive sampling method with 207 respondents. The SEM-PLS method tests the hypothesis on the direct and indirect effects on the research model. Finding/Results: The research findings demonstrate that responsible leadership and psychological empowerment positively impact workforce agility. Furthermore, responsible leadership exhibits a positive influence on psychological empowerment, and this, in turn, indirectly affects workforce agility mediated by psychological empowerment. Conclusion: Private banks have to be able to apply responsible leadership optimally to create workforce agility. Business processes carried out by employees have to be based on psychological empowerment to ensure the quality of work. Workforce agility can improve the quality of financial services to customers by optimizing responsible leadership and psychological empowerment.